Low-Frequency Intrapulmonary Percussive Ventilation Increases Aerosol Penetration in a 2-Compartment Physical Model of Fibrotic Lung Disease - Le Guellec, Sandrine; Allimonnier, Laurine; Heuzé-Vourc’h, Nathalie; Cabrera, Maria; Ossant, Frédéric; Pourchez, Jérémie; Vecellio, Laurent; Plantier, Laurent (Frontiers in Bioengineering and Biotechnology, 2020)
In patients with fibrotic pulmonary disease such as idiopathic pulmonary fibrosis (IPF), inhaled aerosols deposit mostly in the less affected region of the lungs, resulting in suboptimal pharmacokinetics of airway-delivered treatments. Refinement of aerosol delivery technique requires new models to simulate the major alterations of lung physiology associated with IPF, i.e. heterogeneously reduced lung compliance and increased airway caliber. A novel physical model of the respiratory system was constructed to simulate aerosol drug delivery in spontaneously breathing (negative pressure ventilation) IPF patients. The model comprises upper (Alberta ideal throat) and lower airway (plastic tubing) models and branches into two compartments (Michigan lung models) which differ in compliance and caliber of conducting airway. The model was able to reproduce the heterogeneous, compliance-dependent reduction in ventilation and aerosol penetration (using NaF as a model aerosol) seen in fibrotic lung regions in IPF. Of note, intrapulmonary percussive ventilation induced a 2 to 3-fold increase in aerosol penetration in the low-compliance/high airway caliber compartment of the model, demonstrating the responsiveness of the model to therapeutic intervention.